Efficacy of fumaric and citric acids in preventing biosynthesis of aflatoxins in poultry feed with variable moisture content - SINGH, RAM; MANDAL, A B (The Indian Journal of Animal Sciences, 2014)
A poultry feed was prepared using conventional feed ingredients free from aflatoxins. The moisture content of the feed was adjusted at 11, 13, 15 and 17%. The feeds with each level of moisture were then mixed with fumaric or citric acid each at various concentrations of 0.00, 0.05, 0.10, 0.15, 0.20, 0.25, 0.30, 0.35, 0.40, 0.45 and 0.50%. Sample (100 g) from each preparation was taken in duplicate, inoculated with fresh spores of aflatoxins producing mould (Aspergillus parasiticus NRRL 2999), incubated at room temperature for 1 month and then analysed for the presence of aflatoxins (AFB1, AFB2, AFG1 and AFG2). The results showed that at 11% moisture level, none of the 4 aflatoxins were recorded in any of the treatments. However, with the increase in moisture in feed from 11 to 17%, oproduction of aflatoxins increased. The concentrations of AFB1 were 40–60 ppb and total AF 110–170 ppb even at 13% moisture level after 1 month storage of such feed. The biosynthesis of any of the aflatoxins was completely inhibited with 0.20% fumaric acid or 0.45% citric acid in feed containing 13% moisture. However, fumaric or citric acid at 0.50% concentration, failed to completely inhibit synthesis of any of the 4 fractions of aflatoxins in feeds containing 15 and 17% moisture level, though with increased concentrations of acids, biosynthesis of total as well as individual fractions of aflatoxins decreased. It is concluded that storage of feed for 1 month with 13% moisture was not safe. Moreover, the production of AF at 13% moisture level can be completely inhibited by adding fumaric acid @ 0.20% or citric acid @ 0.45%. However, at 15 and 17% moisture level in feed, more than 0.50% of fumaric acid or citric acid is required for complete inhibition of biosynthesis of aflatoxins.